Privatizing the borders: Human rights and the British visa regime (Respond to this article at http://www.therai.org.uk/at/debate). Issue 2 (2nd April 2013) - Kaneff, Deema
<x xml:space="preserve">Abstract</x> This paper explores the 'strengthening' of UK borders through the privatisation of border controls. It looks at the consequences of shifting activities relating to the management of visa applications from the state to the private sector (transnational corporations), and explores the implications this has in terms of human rights and entitlements.